Fetal acalvaria with lateral cleft lip and palate: a rare presentation - Mohd Jamil, Amilia Afzan; Chua, Wang Ching; Valayudham, Vairavan Ramesh; Abu Hassan, Hasyma; Abdul Jalal, Hamidah (Elsevier Inc., 2024)
We report a case of acalvaria diagnosed prenatally via ultrasound and MRI. Acalvaria is a rare, fatal congenital condition characterized by the absence of flat bones of the cranial vault, dura mater, and its associated muscles with an intact central nervous system. A 41-year-old gravida 5, para 2 + 2A, presented to us at 26 weeks gestation age (GA) with ultrasound findings of a fragile and hypomineralized skull in the fetus. The patient was not keen on whole-axon sequencing. Fetus magnetic resonance imaging (MRI) revealed large cutaneous/skull nonvisualization of the fetus skull, possibly acrania without anencephaly. She delivered via cesarean section at 37 weeks because of two previous cesarean sections. A female infant weighing 2650 g was born with an intact sac to minimize excessive external pressure to the brain tissue. A diagnosis of acalvaria with bilateral lateral cleft lip and palate was made postdelivery. The infant was managed conservatively per multidisciplinary discussion and expired 3 weeks later.